Schottky barrier memory based on heterojunction bandgap engineering for high-density and low-power retention - Hyangwoo Kim; Yijoon Kim; Kyounghwan Oh; Ju Hong Park; Chang-Ki Baek (Discover Nano, 2024)
Abstract Dynamic random-access memory (DRAM) has been scaled down to meet high-density, high-speed, and low-power memory requirements. However, conventional DRAM has limitations in achieving memory reliability, especially sufficient capacitance to distinguish memory states. While there have been attempts to enhance capacitor technology, these solutions increase manufacturing cost and complexity. Additionally, Silicon-based capacitorless memories have been reported, but they still suffer from serious difficulties regarding reliability and power consumption. Here, we propose a novel Schottky barrier memory (SBRAM), which is free of the complex capacitor structure and features a heterojunction based on bandgap engineering. SBRAM can be configured as vertical cross-point arrays, which enables high-density integration with a 4F2 footprint. In particular, the Schottky junction significantly reduces the reverse leakage current, preventing sneak current paths that cause leakage currents and readout errors during array operation. Moreover, the heterojunction physically divides the storage region into two regions, resulting in three distinct resistive states and inducing a gradual current slope to ensure sufficient holding margin. These states are determined by the holding voltage (V hold) applied to the programmed device. When the V hold is 1.1 V, the programmed state can be maintained with an exceptionally low current of 35.7 fA without a refresh operation.